Developmental Landmarks and the Warnock Report: A Sociological Account of Biological Translation. (October 2019) - Franklin, Sarah
Abstract: At a crucial meeting during their proceedings, on 9 November 1983, the sixteen members of Britain's influential Warnock Inquiry into Human Fertilisation and Embryology reached a key decision on how to base proposals for comprehensive legislation governing this largely uncharted territory. Famously, they chose the formation of the "primitive streak" in the early embryo as the basis for the fourteen-day rule that has now served as the global benchmark for experimental research in this area for nearly thirty years. Based on newly available archival material and interviews, this article offers a sociological account of the ways in which a specific translation of biological facts became the basis for an enduring social contract governing controversial bioinnovation in the UK. In particular, the combined roles of Committee Chair Mary Warnock and biologist Anne McLaren are examined in terms of how a decision, or "iterative settlement, " was reached as to "where to draw the line" using specific "developmental landmarks" to establish a basis for legal regulation. Drawing from this analysis, I offer a broader argument concerning the sociology of biological translation and biogovernance that is germane to ongoing debates such that over how to limit CRISPR-Cas 9 gene editing. I contend also that we have yet to fully grasp the historical and sociological lessons to be drawn from the early histories of establishing governance over new forms of technological assistance to human reproduction, and in particular the formation of the "Warnock Consensus."